Peculiarities of normal retinal blood supply from the side of retinal pool. - Paltov, E. V. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. One of the causes of eye diseases is the damage of the vascular bed components of the eyeball. Objective. To investigate peculiarities of the rat retinal blood supply from retinal pool. Methods. Adult male rats aged from 4,5–7,5 month were used. To investigate the blood supply of their retina, eye vessels were injected with contrast mass. Results. Vascularization of rat retina on micro-level is realized by the branches of central retinal artery that runs deep in the optic nerve and reaching its disk ramifies providing its vascularization. The main branches that ramify from the central retinal artery run from the area of optic disk to the periphery reaching deep into the layer of nerve fibers. These vessels include numerous arterioles and venules of the retina: dorsolateral, ventrolateral, dorsomedial, ventromedial, ventral and dorsal arterioles and venules of the macula. Each branch of the central retinal artery is divided dichotomously forming arterioles (of the first, second and third order). Near the optic nerve the diameter of arterioles of the first order is 80-100 microns. Subsequently these arterioles are dichotomously divided into second order arterioles with the diameter of 40-50 microns. And the second-order arterioles bifurcate into the third-order arterioles with the diameter of 10-20 microns. Arterioles further bifurcate and enter capillaries with the diameter ranging from 4.0 to 9.0 microns. The dense capillary network was traced over the entire area of the retina. In the deep retinal layers two capillary networks (superficial and deep) were visualized. Superficial capillary network was localized in the deep layer of nerve fibers and is clearly seen in all quadrants of the retina. Deep capillary network lies between the outer plexiform zone and the inner nuclear layer. These two capillary networks are interconnected with the help of anastomoses thus forming a morphological basis for compensatory mechanisms. There are non-vascular areas around the retinal artery located symmetrically on both sides of arteriole. The closer arterioles come to the periphery the more clearly we can see gradual disappearance of the deep capillary network and clear visualization of the surface capillary network dominates with capillaries having a wide diameter. The surface layer capillaries of rat’s retina are running radially from the optic nerve toward the edge of the posterior pole of the retina. Peripapillary capillaries are located at a considerable distance, and are rarely anastomosed to each other. Gradually passing into deeper layers of the retina peripapillary capillaries pass into venules. In the area of optic disk the retina contains another capillary network located in the outermost layer of nerve fibers. Capillaries in this region are located in the radial direction. We also found a capillary network in the normal rat’s retina in the area of macula. Loops of capillaries are polymorphous; they are twice longer than wide and run the same direction as branching arterioles. Retinal peripapillary capillary network is characterized by forward direction of capillaries, they have considerable length, with rarely encountered anastomosis and being located deep in the surface layers of nerve fibers of the retina. Conclusion. It was revealed that there are two capillary networks among rat’s retinal layers. Superficial capillary network is localized deep in the layer of nerve fibers and it is clearly seen in all quadrants of the retinal field. Deep capillary network lies between the outer plexiform zone and the inner nuclear layer. Additionaly capillary network was found in the region of optic disk which is located in the outermost layer of nerve fibers.